2013
DOI: 10.1021/la401566h
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Cross-Linked Bilayer Membranes That Can Incorporate Membrane Proteins from Oligo-Asp-Based Peptide Gemini Surfactants

Abstract: We designed novel bilayer-forming amphiphiles based on the cyclic oligo-Asp-based peptide gemini (PG) surfactants cr-D2C12 and cr-D3C12, which consist of -Cys(Asp)nCys- (n = 2 or 3) as a core peptide and two Cys residues containing a dodecylamidomethyl group. Dynamic light scattering and transmission electron microscopy measurements revealed the formation of spherical bilayer membranes that could incorporate the light-harvesting antenna complex 2 (LH2) from Rhodopseudomonas acidophila . Furthermore, this prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Owing to dimerization of single-chain surfactants, critical aggregation concentrations (CACs) of gemini surfactants are generally smaller than those of the parent single-chain surfactants . As for PG-surfactants, short linear peptides function not only in linking two long alkyl chains into a single molecule, but also as a hydrophilic headgroup. To endow PG-surfactants with amphiphilic properties, the choice of hydrophilic linker peptides is indispensable. However, by adopting hydrophilic peptides at the peripheral peptide (Y-), less hydrophilic peptides can be chosen at linker peptides, without diminishing solubility in an aqueous buffer, enabling a flexible design of various functional PG-surfactants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to dimerization of single-chain surfactants, critical aggregation concentrations (CACs) of gemini surfactants are generally smaller than those of the parent single-chain surfactants . As for PG-surfactants, short linear peptides function not only in linking two long alkyl chains into a single molecule, but also as a hydrophilic headgroup. To endow PG-surfactants with amphiphilic properties, the choice of hydrophilic linker peptides is indispensable. However, by adopting hydrophilic peptides at the peripheral peptide (Y-), less hydrophilic peptides can be chosen at linker peptides, without diminishing solubility in an aqueous buffer, enabling a flexible design of various functional PG-surfactants.…”
Section: Resultsmentioning
confidence: 99%
“…We recently developed a novel class of solubilization surfactants for membrane proteins based on a U-shaped lipopeptide scaffold, consisting of a short linker peptide (-X-) between two long alkyl-chain-modified Cys residues and a peripheral peptide (Y-) at the N-terminal side of alkylamide methylene-modified Cys residues. , We named this scaffold the “peptide gemini surfactant” (PG-surfactant, Figure ) in our previous study . Choosing the betaine peptide sequence -Asp-Lys-Asp-Lys- as the linker peptide (-X-) and the N-terminal acetylated Asp or Lys as the peripheral peptide (Y-), we successfully constructed DKDKC 12 K and DKDKC 12 D as new solubilization surfactants for membrane proteins .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we studied the evolution of several functional molecules from peptide-gemini surfactant (PG-surfactant) molecular framework. The PG-surfactants (Figure ) are a kind of lipopeptide having a gemini-type molecular structure, consisting of two alkyl-chain-modified cysteine residues, a short linker peptide (-X-) between them, and periphery peptides at the N- and C-terminal sides (Y- and -Z, respectively) . In our previous study, by choosing suitable peptide sequences for -X-, Y-, and -Z, we succeeded in designing bilayer-forming amphiphiles, , that could act as solubilization surfactants , and extraction surfactants for membrane proteins; furthermore, these exhibited antimicrobial activities without hemolysis of blood erythrocytic cells . Interestingly, in spite of a simple basic molecular framework, we found a clear relationship between the peptide sequences at the X-, Y-, and Z-positions and the resulting properties and functions of the PG-surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…16−21 The PG-surfactants (Figure 1) are a kind of lipopeptide having a gemini-type molecular structure, consisting of two alkyl-chain-modified cysteine residues, a short linker peptide (-X-) between them, and periphery peptides at the N-and C-terminal sides (Y-and -Z, respectively). 16 In our previous study, by choosing suitable peptide sequences for -X-, Y-, and -Z, we succeeded in designing bilayer-forming amphiphiles, 16,17 that could act as solubilization surfactants 18,19 and extraction surfactants 20 for membrane proteins; furthermore, these exhibited antimicrobial activities without hemolysis of blood erythrocytic cells. 21 Interestingly, in spite of a simple basic molecular framework, we found a clear relationship between the peptide sequences at the X-, Y-, and Z-positions and the resulting properties and functions of the PG-surfactants.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These PG-surfactants (Figure ) are a kind of lipopeptide having a gemini molecular structure, which consists of two alkyl-chain-modified cysteine residues, a short linker peptide (-X-) between them, and periphery peptides at the N- and C-terminal sides (Y- and -Z, respectively) . In our previous study, by choosing the suitable peptide sequences for -X-, Y-, and -Z, we succeeded in designing bilayer-forming amphiphiles, , that could act as solubilization surfactants , and extraction surfactants for membrane proteins. Interestingly, in spite of a simple basic molecular framework, we found that there is a clear relationship between the peptide sequences at the X-, Y-, and Z-positions and the resulting properties and functions of the PG-surfactant.…”
Section: Introductionmentioning
confidence: 99%